2017
DOI: 10.1016/j.ijscr.2017.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty for deltoid-deficient shoulder following latissimus dorsi flap transfer. Case report

Abstract: HighlightsTraumatic shoulder injury resulting in arthritis with loss of the rotator cuff and deltoid muscles.Shoulder muscles reconstruction using a Lattisimus dorsi flap.Preoperative (Arthroplasty) assessment and examination.Preoperative planning prior to shoulder joint reconstruction.Post-operative physiotherapy and follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Dosari et al . also presented in a case report a patient with deltoid deficient shoulder after a history of gunshot injury, who was treated with a RSA after Latissimus dorsi flap and could show a successful treatment with an active abduction of 45° and external rotation of 20° 18 . Nevertheless, as opposed to our case, the viability of the remaining native anterior deltoid (as evident by preoperative needle EMG) was shown preoperatively and the surgical intervention was done in a two‐stage approach.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Dosari et al . also presented in a case report a patient with deltoid deficient shoulder after a history of gunshot injury, who was treated with a RSA after Latissimus dorsi flap and could show a successful treatment with an active abduction of 45° and external rotation of 20° 18 . Nevertheless, as opposed to our case, the viability of the remaining native anterior deltoid (as evident by preoperative needle EMG) was shown preoperatively and the surgical intervention was done in a two‐stage approach.…”
Section: Discussionmentioning
confidence: 54%
“…Shoulder soft tissue coverage using LDMF has also been reported in several studies 3,15,16 . Nevertheless, the functional reconstruction of the shoulder musculature using the pedicled LDMF has only been described to our knowledge in two case reports 17,18 . Paprottka et al .…”
Section: Discussionmentioning
confidence: 98%
“…We propose that deltoid insufficiency is related to as opposed to an absolute contraindication to RSA in a select patient population. In previous reports, patients with partial deltoid function had demonstrated favorable RSA outcomes [6][7][8][9][10]. To our knowledge, this case report is the first to present the ability of RSA to treat practically complete deltoid insufficiency (especially in the middle deltoid and posterior deltoid fibers) due to corticosteroid usage in a patient with SLE.…”
Section: Discussionmentioning
confidence: 60%
“…In that case, the patient was treated with a latissimus dorsi muscle flap because of the deltoid muscle deficiency, followed by RSA. Essilfie et al [ 10 ] and Goel et al [ 9 ] each reported a case where a latissimus dorsi muscle flap was used to treat deltoid muscle deficiency [ 8 ]. An RSA procedure after latissimus dorsi flap in patients with deltoid deficiency can be a successful and reproducible approach to treat such conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation